PEMBINAAN MINAT SASTRA ANAK MELALUI PELATIHAN MENULIS PUISI BEBAS DENGAN AKSARA ARAB MELAYU DI MDTA MUHAMMADIYAH SIGIRING GIRING DAN MDTA MUHAMMADIYAH SADABUAN - Idawati Idawati; Nikmah Sari Hasibuan; Adek Nurkholija (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
This Community Service PKM aims to provide training to students in fostering interest in writing free poetry in Arabic-Malay script. This activity was carried out for three months for MDTA Muhammadiyah students Sigiring at Kayu Ombun. The number of partner members in this activity is 10 people. The methods used in this activity consist of; preparation and socialization, coaching and assignment as well as training, monitoring and evaluation. The results obtained were that the students became more proficient in writing poetry using Arabic-Malay script. Thus this activity.